2020
DOI: 10.1001/jamanetworkopen.2020.6016
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of US Adolescents and Adults With Sickle Cell Disease on Their Quality of Care

Abstract: IMPORTANCE Sickle cell disease (SCD) is the most common inherited red blood cell disorder in the United States, and previous studies have shown that individuals with SCD are affected by multiple health disparities, including stigmatization, inequities in funding, and worse health outcomes, which may preclude their ability to access quality health care. This needs assessment was performed as part of the Sickle Cell Disease Implementation Consortium (SCDIC) to assess barriers to care that may be faced by individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Findings from our needs assessment within our 5-county region mirror needs assessment results from the broader consortium. 51 The SCDIC has prioritized developing an intervention that addresses the challenges identified within the care process domain by directly enhancing provider access to patient individualized care plans in the electronic health record in the ED. Importantly, ED providers will be asked to view a short video that directly challenges bias and stigma in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from our needs assessment within our 5-county region mirror needs assessment results from the broader consortium. 51 The SCDIC has prioritized developing an intervention that addresses the challenges identified within the care process domain by directly enhancing provider access to patient individualized care plans in the electronic health record in the ED. Importantly, ED providers will be asked to view a short video that directly challenges bias and stigma in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are consistent with findings from the national sample of adults with SCD who participated in the ASCQ-Me field test, and with results from the SCDIC needs assessment. 33,51 Interviews and surveys are subject to self-report bias and, therefore, may or may not reflect the actual behaviors or thoughts of participants. Confidence is increased in our results given the triangulation of expressed concerns across participant groups and across data collection strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33] Unfortunately, recent studies continue to demonstrate that BIPOC patients presenting with painful conditions continue to face disadvantages regarding assessment and treatment in EDs, [34][35][36][37][38] with patient perceptions of this disparity serving as a barrier to even seeking emergency care. 39 Similarly, a 2018 study of traumatically injured individuals requiring emergency medical services (EMS) transport to hospitals found that significantly fewer Black patients received opioids prehospital compared to other ethnic groups. 40 Similar findings were obtained from a more recent study.…”
Section: Racism In Pain Medicine: a Review Of The Literaturementioning
confidence: 99%
“…In the survey described, participants with severe pain or 4 or more pain episodes in the previous 6 months were much less likely to be satisfied with their scheduled nonacute appointments. 2 In addition, patients with SCD that report experiences of discrimination are 53% more likely to report nonadherence to physician treatment recommendations. 3 Mistrust in health care professionals has been shown to be a mediator of the discrimination-nonadherence relationship.…”
mentioning
confidence: 99%